Study of new spring common wheat samples from the world collection in the conditions of the Ryazan region - T. A. Barkovskaya; O. V. Gladysheva; E. V. Zuev; V. G. Kokoreva (Зерновое хозяйство России, 2024)
In the conditions of the Ryazan region there have been studied 64 spring common wheat varieties from the collection of the Federal Research Center VIGRR named after Vavilov in order to identify valuable traits for use in breeding. Field trials were carried out in the collection nursery on dark gray forest heavy loamy soil in 2018–2022, using the methodological recommendations of the Federal Research Center VIGRR named after Vavilov. There has been established that the highest yields (more than 5.0 t/ha) were formed by the varieties ‘Arseya’, ‘Maestro’ (Ryazan region), ‘KWS Akvilon’, ‘Ethos’ (Germany), ‘KWS Torridon’ (Great Britain), ‘Odeta’ (Czech Republic), ‘Calispero’ (France), which was on 29.9–49.9 % higher than the mean variety productivity in the trial. Yield stability with the least variation (Cv) was established for the varieties from the Central region – RIMA, ‘Arseya’ (Ryazan region), ‘Zlata’ (Moscow region) and ‘Omskaya 36’ (West Siberian region) with 3.1–9.6 %. The studied assortment of plant heights was divided into groups, such as dwarfs (< 60 cm) – 4.7 %, semi-dwarfs – 12.5 %, medium-sized – 75.0 %, tall – 7.8 %. There were identified 8 early ripening varieties ‘Chelyaba 2’ (Chelyabinsk region), ‘Odeta’ (Czech Republic), ‘Zlata’ (Moscow region), ‘Novosibirskaya 29’, ‘Novosibirskaya 15’, ‘Polyushka’ (Novosibirsk region), ‘M-83-1531’ (USA), ‘Burlak’ (Ulyanovsk region). The varieties ‘Voevoda’ and ‘Favorit’ (Saratov region) showed high resistance to various pathogens. There has been found a strong correlation between productivity and the density of productive stems with r = 0.753±0.084. 0.808±0.075, an average correlation with a number of grains per head with r = 0.427±0.115. 0.716±0.089 and grain weight per head with r = 0.374±0.118...0.689±0.092. Grain weight per head was largely determined by a number of grains per head with r = 0.621±0.099. 0.824±0.072.